The Transition from School to Jail: Youth Crime and High School Completion Among Black Males - Antonio Merlo
In this paper, we propose a new approach to the empirical study of the relationships among schooling, youth employment and youth crime which provides a comprehensive analysis of the dynamic interactions among these choices and exposure to the criminal justice system. The empirical framework takes the form of a multinomial discrete choice vector autoregression of a youth’s schooling, work and crime decisions as well as arrest and incarceration outcomes. We allow for observable initial conditions, unobserved heterogeneity, the possibility of measurement error and for missing data. We use data from the NLSY97 on black male youths starting from age 14. The estimates indicate an important role for heterogeneity in initial conditions. We also find that stochastic events that arise during one’s youth can be important in determining outcomes as young adults.crime, schooling, work, VAR